Analisis Penanaman Nilai Ikhlas Taat Khauf dan Taubat melalui Metode Khusus Pembelajaran PAI untuk Tingkat SD/MI - Luqyana Lutfi Hana; Qoni Lathifatul Hidayah; M. Imamul Muttaqin (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to provide an understanding of the values of sincerity, obedience, khauf, and repentance. In addition, this article also discusses the application of special learning methods for Islamic Religious Education (PAI) at the elementary / middle school level that are appropriate to instill the values that have been mentioned. This research is qualitative through a literature approach by examining various related literature. In the midst of the challenges of globalization that cause the erosion of religious values, the cultivation of these values is very important. The results of the study show that the method of lecture, ibrah, and exemplary is effective if used in instilling these values in students. The lecture method can play a role in conveying the material directly, while the ibrah and exemplary method can encourage student understanding through various stories and direct examples.